Optical imaging in biomedicine - Olivo, Malini (Henry Stewart Talks, 2010)
What is biophotonics?, The need for biophotonics in medicine, Photomedicine in cancer, In vivo optical imaging in cancer detection, Endoscopic optical biopsy, Real-time clinical fluorescence diagnostic system, Image analysis algorithm, Diagnostic accuracy of bladder and oral cancer detection using fluorescence, Macroscopic fluorescence analysis in the oral cavity and cervix, Ex-vivo optical methods, Autofluorescence lifetime studies, Towards a 3D fluorescence in vivo cellular diagnostic system, Optical coherence tomography (OCT), OCT vs. confocal imaging, Nano-oncology, Nano-based imaging, Nano-drug delivery systems